The ODHeatMap tool: Open data district heating tool for sustainable energy planning - Diana Moreno; Steffen Nielsen; Meng Yuan; Frederik Dahl Nielsen (International Journal of Sustainable Energy Planning and Management, 2024)
Building footprints are a geographical indication of the spatial distribution of built-up infrastructure, thereby reflecting energy demand patterns, including heating requirements. Heating demands spatial distribution shown in heat atlases are primordial for evaluating district heating systems feasibility, which are a key decarbonizing technology that offers more sustainable heat supply in dense urban areas. Sustainable energy planning frameworks utilize district heating potentials as metrics for the formulation of alternate system configurations aimed at decarbonizing societies and creating an understanding of heating transition pathways. However, the availability and accessibility of the data needed for assessing these potentials is highly contextual and often challenges modelling processes. Simultaneously, there is a growing potential for open data and software mechanisms that could aid in addressing these challenges and create otherwise unavailable heat mapping resources. This paper describes the development of the ODHeatMap tool, a workflow built with open data in python functions that transform building footprints into a heat atlas. Ulaanbaatar city is used as a demonstration area for the tools functionalities, with the outputs being applied in a broader study aimed at developing strategies for Mongolia's heating sector. The tool is accessible through a fully cloud-based environment and can be used in any given geographical context.